(untitled) (Journal of Economic Research & Business Administration, 2018)
The necessity of socio-economic development and investment attractiveness of the regions is shown. The urgency of an assessment and forecasting of investment attractiveness of the region, for advancing formation of budgetary and off-budget part of investment expenses is revealed. The novelty of the research consists in the systematization of retrospective and statistical data, modeling the impact of socioeconomic development indicators on the volume of the gross regional product. Methods of theoretical and empirical research, as well as methods of mathematical modeling were applied. The analysis of existing theoretical studies on the investment attractiveness of the region and its components. It is shown that the investment attractiveness should be defined as an economic category, allowing a potential investor to make judgment on the combination of regional factors and to determine the capabilities and limitations of the implementation of the investment interests in the investment of capital into the region in the present and future periods. The necessity of the model of indirect estimation of investment attractiveness allowing to plan investment activity and to raise the level of social and economic development of the region is revealed. Indicators of socio-economic development for the regression analysis were determined. The method of estimation of investment attractiveness of regions is offered, developed with application of provisions of the theory of systems, namely the principles of necessary variety of elements, minimum sufficiency and their target orientation which in turn is very valuable for the potential investor.